An electrode-grounded droplet-based electricity generator (EG-DEG) for liquid motion monitoring - Yang, Lei (2023)
Triboelectric nanogenerator (TENG) is a potential technology for harvesting water energy and serving as self-powered sensors. Among the innovative designs of TENG, a droplet-based electricity generator (DEG) has achieved high instantaneous power density under droplets impinging. However, the exposed top electrode is usually hydrophilic and subjected to water corrosion. This study reports an electrode-grounded droplet-based electricity generator (EG-DEG) with graphene sheets embedded carbon (GSEC) electrode. Compared with traditional electrodes, the designed device with GSEC electrode exhibits great hydrophobicity, corrosion resistance under droplets impinging and better output performance. The working mechanism of the device is discussed in depth and the performance of EG-DEG is systematically studied. To demonstrate the robust capability of EG-DEG as self-powered sensors, a three-electrodes mode of EG-DEG is developed to monitor droplet velocities on different triboelectric surfaces. Furthermore, the EG-DEG can be assembled in the pipe to acquire the flow rate of fluid according to the frequency of the output signals. An intelligent system is further developed to display the flow rate of the fluid. Therefore, the EG-DEG device also shows its great application prospects in particles detection and fluid analysis in the future.